Penerapan Metode Eja Terhadap Kemampuan Menulis Permulaan di Kelas I Sekolah Dasar Negeri No 104265 Lestari Dadi - nurul fauziah; Sujarwo (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
Writing ability is one of the productive language skills, meaning that with the ability to read and write students can produce a work in written form. Many things are involved when someone writes. Think regularly and logically, be able to express ideas clearly, and be able to use language effectively and apply rules in writing. Based on the results of the initial observations I made regarding the conditions at the research site, it was seen that in applying writing skills in class I, the teacher did not apply various writing methods. This is evidenced by the fact that students feel bored and bored when the learning process is taking place. In addition, after observing, it is known that the problem that occurs is because students have not been able to write simple words correctly, and still spell every word they read, as a result students do not understand what the teacher says in class. The formulation of the research problem is how is the ability to write the beginning before applying the spelling method in class I State Elementary School No. 104265 Lestari Dadi? How is the initial writing ability after applying the spelling method in class I of State Elementary School No 104265 Lestari Dadi? Is there an increase in students' initial writing ability after applying the spelling method in class I of State Elementary School No 104265 Lestari Dadi? The purpose of this study was to determine the initial writing ability before applying the spelling method in class I State Elementary School No. 104265 Lestari Dadi. To determine the initial writing ability after applying the spelling method in class I State Elementary School No 104265 Lestari Dadi. To find out the improvement of students' initial writing skills after the spelling method was applied in class I of State Elementary School No. 104265 Lestari Dadi. This study used 40 students as a sample of 208 students. Data retrieval is done by holding a pretest and posttest spelling method. The results showed that the application of the spelling method to the initial writing ability of first-class students showed good results. The spelling method is effective in improving early writing skills. This is evidenced by the initial writing ability before the spelling method is applied has an average of 72.05, and after the spelling method is applied it has an average of 82.3. This has experienced a significant increase. From the results obtained, it can be concluded that there is an increase in initial writing ability after applying the spelling method to the first grade students of State Elementary School No. 104265 Lestari Dadi. Keywords: Spell Method, Beginning Writing Ability